CURRENT TREATMENT OF VENOUS THROMBOEMBOLIC COMPLICATIONS WITH ANTICOAGULANTS: APIXABAN - I. S. Yavelov («REMEDIUM GROUP» Ltd., 2015)
The article presents the review of clinical studies that determined the role of apixaban in the early treatment and long-term secondary prophylaxis of deep vein thrombosis and lower limbs and and/or pulmonary arteries embolism. It also defines a patient population for whom apixaban administration is justified on the basis of pilot studies and the clinical data accumulated to date at various clinics.